Предмет:
МатематикаАвтор:
аноним-2/9 * (2,7 * х - 1 1/2 * у) - 1 1/6 * (2,4 * х - 1 5/7 * у) = -2/9 * 27/10 * х + 2/9 * 3/2 * у - 7/6 * 24/10 * х + 7/6 * 12/7 * у = -3/5 * х + 1/3 * у - 14/5 * х + 2 * у = -(3/5 + 14/5) * х + (1/3 + 2 * 3/3) * у = -17/5 * х + 7/3 * у;
Ответ: -17/5 * х + 7/3 * у.
Автор:
verenaДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть